Use of Platelet-Rich Fibrin in the Treatment of Periodontal Intrabony Defects: A Systematic Review and Meta-Analysis. (4th February 2021) - Chen, Liang; Ding, Yi; Cheng, Guoping; Meng, Shu
Abstract : Background . Platelet-rich fibrin (PRF) is a kind of autologous platelet concentrate which is easy to obtain and cheap. In recent years, it has been studied to improve the effect of periodontal regeneration. However, few studies have systematically evaluated the complementary effect of PRF in the treatment of intrabony defects. The present review is aimed at systematically assessing the effects of PRF on clinical and radiological outcomes of the surgical treatment of periodontal intrabony defects. Methods . The protocol was registered at PROSPERO (International Prospective Register of Systematic Reviews) as CRD42020206056 . An electronic search was conducted in MEDLINE, Cochrane, and EMBASE databases. Only randomized clinical trials were selected. Systematically healthy patients with two or three walls of intrabony defects were considered. Intrabony defect (IBD) depth reduction and bone fill (BF) % were set as primary outcomes while probing depth (PD) reduction, clinical attachment level (CAL) gain, and gingival margin level (GML) gain were considered as the secondary outcome. When possible, a meta-analysis was performed. Results . Eighteen articles fulfilled the inclusion criteria, and seventeen studies were quantitatively analyzed. Of 17 studies, four were rated as high risk of bias and thirteen as the moderate risk of bias. Two comparisons were set: (1) open flap debridement (OFD) combined with PRF and OFD alone and (2) bone grafting (BG) combined with PRF and BG alone. Compared to OFD alone, OFD+PRF showed significantly greater in all primary and secondary outcomes. Compared to BG alone, BG+PRF showed significantly greater in IBD depth reduction, PD reduction, CAL gain, and GML gain. Conclusions . The use of PRF was significantly effective in the treatment of periodontal intrabony defects. The benefit of OFD+PRF may be greater than BG+PRF. PRF can promote early wound healing in periodontal surgery. As all included studies were not at low risk of bias, well-designed RCTs having a high methodological quality are needed to clarify the additional effectiveness of PRF in the treatment of intrabony defects in the future.